Constructing the Longmen Shan eastern Tibetan Plateau margin: Insights from low‐temperature thermochronology. Issue 3 (7th June 2013) - Tian, Yuntao; Kohn, Barry P.; Gleadow, Andrew J. W.; Hu, Shengbiao
Abstract [1] Contrasting models of upper crustal shortening versus lower crustal flow have been proposed to explain the formation of thickened crust in the Longmen Shan (LMS), eastern Tibetan Plateau (TP) margin. These models require different structural kinematics along the LMS, whose structural geometry is defined by three parallel NW‐dipping fault zones. From foreland (southeast) to hinterland (northwest), they are the Guanxian‐Anxian Fault, Yingxiu‐Beichuan Fault (YBF), and Wenchuan‐Maowen Fault (WMF). Newly derived and previously published low‐temperature thermochronology data from the LMS were synthesized to constrain the spatial exhumation and test previous models. The results show that (1) exhumation increases abruptly across the range‐bounding YBF, suggesting the fault being the main thrust boundary between the LMS and the Sichuan Basin to the east; (2) Younger Late Cenozoic cooling ages are found on the hinterland WMF, where a dichotomy of ages on the hanging wall versus footwall suggests Late Cenozoic thrust activity; and (3) toward the hinterland to the west, exhumation rates decrease twofold over a distance of 30–40 km. This exhumation pattern indicates a westward decrease of tectonic uplift, providing the regional topography approached a steady state, whereby exhumation is in balance with tectonic uplift. The observed exhumation estimates support an upper crustal configuration where thrusts in the LMS merge gradually into a gentle detachment seated at a depth of 20–30 km. Results of this study support a revised upper crustal thrusting model.